The Effectiveness of Link System in Teaching Speaking at SMA Yadika Baturaja - Yunda Lestari (Jurnal Didascein Bahasa, 2016)
ABSTRACT: This study was aimed at finding out whether or not link systemsignificantly effective in teaching speaking to the eleventh grade students ofSMA Yadika Baturaja. This study used pre-experimental method by taking oneclass as the sample of the study. The population of this study was the eleventhgrade students of SMA Yadika Baturaja with the total number were 212students in academic year 2014/2015. The sample was 35 students in one classwhich was chosen by using purposive sampling. The data obtained through theoral test and was analyzed by using paired sample t-test of SPSS 16 program.The result of the study showed that the average students’ scores in post-test(62.16) was higher than the average students’ scores in pre-test(55.39). Theresult of the data analyzed through SPSS 16 program was 5.477to tobtained and 2.032 to ttable with the significance level ( = 0,05) and degree α of freedom (df = 35– 1 = 34) which means that it was significantly effective to teach speaking byusing link system to the eleventh grade students of SMA Yadika Baturaja.Key words: effectiveness, mnemonic, link system.